2018
DOI: 10.1016/j.cattod.2017.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the differences in catalytic performance for hydrogen production of Ni and Co supported on mesoporous SBA-15

Abstract: Highlights-Ni-Co/SBA-15 catalysts has been prepared from highly dispersed Ni/Co silicate-Nickel yields a high dispersed metallic phase and a stable catalytic performance-A bimetallic phase is formed mainly located in the channels of SBA-15 support-Co segregation to the surface destabilizes and increases the particle size *Highlights (for review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
(40 reference statements)
0
12
0
Order By: Relevance
“…CeO 2‐x goes through reduction/oxidation cycles along the reaction, enhancing oxygen mobility and coke gasification, thus improving the catalyst stability. Accordingly, an intimate contact between ceria and the active metal phase (coke promoter) should facilitate the process, and this can be addressed by using a high surface support [32–34] . On the other hand, a proper dispersion of the active metal phase has been shown to reduce graphitic coke formation by suppressing methane decomposition (the main source of coke at high temperatures), [35,36] a structure‐sensitive reaction which is favored in larger crystal [37,38] .…”
Section: Introductionmentioning
confidence: 99%
“…CeO 2‐x goes through reduction/oxidation cycles along the reaction, enhancing oxygen mobility and coke gasification, thus improving the catalyst stability. Accordingly, an intimate contact between ceria and the active metal phase (coke promoter) should facilitate the process, and this can be addressed by using a high surface support [32–34] . On the other hand, a proper dispersion of the active metal phase has been shown to reduce graphitic coke formation by suppressing methane decomposition (the main source of coke at high temperatures), [35,36] a structure‐sensitive reaction which is favored in larger crystal [37,38] .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Ni‐based catalysts are widely investigated due to low cost and relatively high activity . However, Ni is prone to coke deposition and particle sintering . Coke deposition originates mainly from CH 4 decomposition [Eq.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] However, Ni is prone to coke deposition and particle sintering. [9] Coke deposition originates mainly from CH 4 decomposition [Eq. (2)] and/or Boudouard reaction [Eq.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative strategy to overcome this issue involves the use of bimetallic systems, where the synergistic effects of the two metals can improve their catalytic performances. In this sense Ni-Co is one of the most popular couple being used for this SRE reaction but also for reforming of methane [19,[22][23][24][25][26]. It has been previously reported that the combining effect of this two metals is able to produce less amount but also less harmful carbon deposits [6].…”
Section: Introductionmentioning
confidence: 99%